Barbershops as a setting for supporting men's mental health during the COVID-19 pandemic: a qualitative study from the UK. Issue 4 (27th July 2022) - Ogborn, Georgina; Bowden-Howe, Cerys; Burd, Patsy; Kleijn, Maya; Michelson, Daniel
Abstract : Background: Previous research has highlighted the need to promote help-seeking by men with mental health problems. Aims: To investigate barbers' views about offering mental health support for men in barbershops, with a specific focus on the psychosocial impacts of the COVID-19 pandemic. Method: We used a sequential mixed-methods qualitative design with online data collection. In Phase 1, 30 barbers in Southern England completed surveys exploring perceptions of their clients' mental health during the COVID-19 pandemic, experiences of informal supportive roles and scope for providing formal mental health support in barbershops. Phase 2 involved member validation interviews and explored practice implications with three Phase 1 respondents. Results: Thematic analysis identified three overarching themes: 'more than a haircut' (describing how the physical and relational contexts of barbershops can offer a supportive environment for clients); 'impacts of COVID-19' (describing stressors related to the pandemic and implications for clients' mental health and barber–client relationships); and 'formal mental health strategies' (describing opportunities for, and potential barriers to, formalising mental health support in barbershops). Conclusions: Barbers were aware of their clients' worsening mental health during the COVID-19 pandemic. Barbershops were generally considered to be a suitable setting in which to promote good mental health, monitor for signs of mental ill health and provide information about local mental health services. Future work is needed to co-produce and evaluate formal mental health promotion and prevention strategies in barbershops. Particular attention should be given to service innovations that preserve the credibility and trust that are fundamental to the barbershop experience for many males.